The Impact of Leadership, Motivation, Discipline, and Wages on The Performance of Sharia Bank Employees - Noviarita, Heni; Ahmad, Roslee Bin; Fautau, Idzam (Economica: Jurnal Ekonomi Islam, 2021)
Abstract:  The development of Islamic Banks increased rapidly. Based on assets, profitability, market share, and others. They were followed by internal management, such as an expansion of the facilities and services. On the other hand, considering Islamic Banks’ human resources is very important in realizing the vision and mission. As a result, they must be improving the worker's performance on the goals. This research used a quantitative approach with the independent variable are leadership, working discipline, motivation, and wages. The dependent variable used in this research is employee performance. The result showed that leadership, working discipline, motivation, and wages significantly affect the employee enterprise. It can be seen from the magnitude of t count of 45.804 > t table of 2.51 with a significance (sig) of 0.000 < 0.05. Simultaneously critical in the leadership thorough giving higher wage and the reward encouraged workers’ motivation, discipline to increase workers’ performance. As a result, those variables can improve employee performance to achieve a manner together in Bank BRI Syariah Tugumulyo Branch, Bandar Lampung, South Sumatra. The conclusion stated that the independent variables affected the workers' enterprise. Therefore, as a result, these models are very suitable for improving banks’ workers to achieve their goals.Abstrak: Perkembangan Bank Syariah meningkat pesat. Berdasarkan aset, profitabilitas, pangsa pasar, dan lain-lain. Disusul dengan manajemen internal, seperti perluasan fasilitas dan layanan. Di sisi lain, mengingat sumber daya manusia Bank Syariah sangat penting dalam mewujudkan visi dan misi. Akibatnya, mereka harus meningkatkan kinerja pekerja pada tujuan. Penelitian ini menggunakan pendekatan kuantitatif dengan variabel bebas yaitu kepemimpinan, disiplin kerja, motivasi, dan upah. Variabel terikat yang digunakan dalam penelitian ini adalah kinerja karyawan. Hasil penelitian menunjukkan bahwa kepemimpinan, disiplin kerja, motivasi, dan upah berpengaruh signifikan terhadap karyawan perusahaan. Hal ini terlihat dari besarnya t hitung sebesar 45,804 > t tabel sebesar 2,51 dengan signifikansi (sig) sebesar 0,000 < 0,05. Sekaligus kritis dalam kepemimpinan menyeluruh memberikan upah yang lebih tinggi dan penghargaan mendorong motivasi pekerja, disiplin untuk meningkatkan kinerja pekerja. Sehingga variabel-variabel tersebut dapat meningkatkan kinerja pegawai untuk berprestasi secara bersama-sama di Bank BRI Syariah Cabang Tugumulyo, Bandar Lampung, Sumatera Selatan. Kesimpulannya menyatakan bahwa variabel independen berpengaruh terhadap perusahaan pekerja. Oleh karena itu, sebagai hasilnya, model ini sangat cocok untuk meningkatkan pekerja bank untuk mencapai tujuan mereka.